2023
DOI: 10.1021/acs.jpclett.3c00709
|View full text |Cite
|
Sign up to set email alerts
|

Facet Engineering: A Promising Pathway toward Highly Efficient and Stable Perovskite Photovoltaics

Abstract: right pane is the description of the local crystal direction change along the black arrows. Reproduced with permission from ref 37. Copyright 2019 Elsevier Inc. (e and f) Atomic-resolution STEM images of the stacking fault GBs and twinning GBs. Reproduced with permission from ref 38.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…As shown in Figure S9, I and Pb atoms are distributed uniformly on the (100) and (111) facets. It was also reported that the (100) facet has a lower trap state density than the (111) facet. , Thus, we can exclude the possibility that the specific (100) passivation could be attributed to the different surface compositions or the high trap state density. Piezoresponse force microscopy (PFM) and Kelvin probe force microscopy (KPFM) can provide further insights into the nature of (100) and (111) facets. , As shown in Figure A and B, it is found that the (100) facet exhibits almost opposite polarity direction compared with the (111) facet, and work function (WF) values of the (100) facet are lower than those of the (111) facet.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…As shown in Figure S9, I and Pb atoms are distributed uniformly on the (100) and (111) facets. It was also reported that the (100) facet has a lower trap state density than the (111) facet. , Thus, we can exclude the possibility that the specific (100) passivation could be attributed to the different surface compositions or the high trap state density. Piezoresponse force microscopy (PFM) and Kelvin probe force microscopy (KPFM) can provide further insights into the nature of (100) and (111) facets. , As shown in Figure A and B, it is found that the (100) facet exhibits almost opposite polarity direction compared with the (111) facet, and work function (WF) values of the (100) facet are lower than those of the (111) facet.…”
Section: Resultsmentioning
confidence: 83%
“…It was also reported that the (100) facet has a lower trap state density than the (111) facet. 32,33 Thus, we can exclude the possibility that the specific (100) passivation could be attributed to the different surface compositions or the high trap state density. Piezoresponse force microscopy (PFM) and Kelvin probe force microscopy (KPFM) can provide further insights into the nature of (100) and (111) facets.…”
Section: Mechanisms Of Facet-dependent Passivationmentioning
confidence: 99%
“…[ 3,10 ] Further enhancement of photovoltaic performance is mainly restricted by defects and impurities that exacerbate non‐radiative recombination of photogenerated charge carriers. [ 11–14 ] As a relative mature strategy, intensive efforts have been made on surface defect passivation to solve this issue. For instance, organic ammonium halide salts with different chain lengths have been conventionally used as surface passivator, yet it is still hard to mitigate the defects and impurities inside the bulk.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15–17 ] In addition to fill the corresponding ion vacancy defects and diminish deep energy level traps, the introduction of appropriate Cs + and Br − into FAPbI 3 ‐based perovskite films can also improve the phase stability of FAPbI 3 . [ 13,14 ] Although surface treatment can achieve longitudinal diffusion of some elements inside the film, it requires stricter solvent compatibility with perovskite, and the concentration of dopants is limited by the type of solvent. For example, alkali halide salts can be almost only resolved in polar solvents like water and isopropanol, but these solvents are extremely corrosive to perovskite films.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work has also proven that modifying perovskite films can improve device efficiency and stability. , Nevertheless, the majority of passivating molecules feature only a single active site (N, O, or S electron donor) capable of interacting with uncoordinated Pb 2+ . Even molecules with multiple active sites, such as polymers, face challenges simultaneously passivating defects due to steric hindrance. To fully harness the capabilities of Lewis base defect passivation, it is crucial to develop and fine-tune multiactive-site passivating molecules that effectively reduce interfacial nonradiative recombination losses.…”
mentioning
confidence: 99%